Surgical repair of acute Achilles tendon rupture with and without human amniotic membrane augmentation: a retrospective comparative study - Chien, Ju Chun; Kuo, Meng Chen; Chou, Yi Jiun; Wei, Yi Ping (Frontiers in Surgery, 2025)
ObjectivesAchilles tendon ruptures are common, particularly in active individuals; however, optimal healing remains challenging due to limited vascularity, adhesions, and re-rupture risk. Human amniotic membrane (hAM), rich in extracellular matrix and bioactive factors, shows regenerative potential, offering a promising adjunct for tendon repair.MethodsAfter institutional review board approval, patients aged 20–75 years who underwent end-to-end Achilles tendon repair for acute complete rupture between February 2019 and January 2025 were retrospectively reviewed. Patients were grouped by intraoperative use of hAM allografts. Baseline characteristics, rupture location, operative time, complications (tendon re-rupture, wound infection, dehiscence), American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot score, and follow-up duration were analyzed using t-tests and Fisher's exact tests (p < 0.05).ResultsIn total, 45 repairs were performed in 44 patients. Of these, 13 patients (13 feet) received hAM augmentation, while 31 patients (32 feet) underwent primary repair without hAM. The overall mean follow-up time for the entire cohort was 38.16 ± 21.13 months. Complications occurred in 11 of the 45 feet, including 1 wound dehiscence, 3 re-rupture (2 of which were associated with wound infection), and 7 additional cases of wound infection. Operative time was significantly shorter in the hAM group (94.00 ± 30.12 vs. 116.72 ± 24.46 min, p = 0.011), with no significant differences in complication rates or AOFAS scores. Ruptures closer to the calcaneal insertion were associated with higher infection risk (2.86 ± 1.41 cm vs. 4.36 ± 1.14 cm, p = 0.002). Complications correlated with lower AOFAS scores (p < 0.0001), independent from hAM use.ConclusionsThe hAM augmentation reduced operative time without affecting complication rates or functional outcomes. Further prospective studies are needed to confirm its clinical benefits.Level of evidence: IV.